Solidarność 1980-1985 [ulotka z powielonym logotypem] . Solidarność 1980-1985. Flier with multiplied logo (Polska, 1985)
Red print on white paper. Poster includes a graphic image which represents the Solidarity logotype multiplied 5 times, with a Polish flag.